Development and Analysis of Semi-Interpenetrating Polymer Networks for Brain Injection in Neurodegenerative Disorders. Issue 11 (November 2013) - Tunesi, Marta; Batelli, Sara; Rodilossi, Serena; Russo, Teresa; Grimaldi, Annalisa; Forloni, Gianluigi; Ambrosio, Luigi; Cigada, Alberto; Gloria, Antonio; Albani, Diego; Giordano, Carmen
Purpose: Our aim was to assess the use of injectable, biocompatible and resorbable, hydrogel-based tools for innovative therapies against brain-related neurodegenerative disorders like Alzheimer's (AD) and Parkinson's (PD) diseases. Methods: Two compositions of semi-interpenetrating polymer networks (semi-IPNs) based on collagen and poly(ethylene glycol) (PEG) were investigated. We examined their viscoelastic properties, flow behavior, functional injectability, as well as in vitro biocompatibility with SH-SY5Y human neuroblastoma cells and murine primary neurons. We also evaluated the in vivo biological performance after subcutaneous and brain injection in mice. Results: The selected semi-IPNs showed a gel-like behavior and were injectable through a 30 G needle, with the maximum load ranging from 3.0 to 3.9 N. In vitro results showed that immortalized cells kept their proliferative potential and neurons maintained their viability after embedding in both materials, with better performances for the gel with the higher collagen content. For both semi-IPNs, after subcutaneous injection, the inflammatory response was negligible; after brain injection, the tissue did not show any signs of damage or degeneration. Conclusions: The results suggest that the selected semi-IPNs not only represent a proper environment for cells, but also, once injected in vivo, do not induce damage/inflammation in the surrounding brain tissue. These findings represent a crucial starting point for the development of minimally invasive and injectable hydrogel-based tools for innovative drug/cell-based therapeutic strategies against AD, PD, or other severe brain-related neurodegenerative pathologies.